Activación de dos herbicidas y su incidencia en el control de caminadora (Rottboellia exaltata (L)) en un cultivo de sorgo (Sorghum bicolor (L) Moench) ubicado en un suelo de vega - Otero Gil, Víctor Gabriel (Universidad de los Llanos, 2018)
An axperiment with growing chicks was conducted at ICA 's experiment station, Tibaitata, in the [Jo gota ploteau, to study the effect af adding cy~ nide (363 mg KCN/kg) and tann;ns ( 10 g/kg) to sorghum and corn basedrations, and the oction of thiosulfate and choline in preventing the toxic - effects of cyanide and tonnias respectively.